What Would a Development-Friendly WTO Architecture Really Look Like? - Subramanian, Arvind (IMF Working Papers; Working Paper, 2003)
This paper elaborates on a number of key principles that need to underpin a coherent and development-friendly architecture for the WTO. The key principles include enlarging the scope of WTO bargaining to include labor flows as well as capital flows; creating a structure that would provide a balance between furthering liberalization and providing some discretion or policy space to accommodate the inevitable political constraints; and minimizing the extent of regulatory harmonization. These principles, while applicable to all countries, may have less immediate relevance in addressing the problems of the least developed countries.